Penataan Kawasan Wisata Danau Bandar Khayangan Di Pekanbaru Dengan Pendekatan Arsitektur Tepian Air - Dwihapsari Lestarining Tyas; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bandar Khayangan Lake Tourist Area is a tourist attraction located in the Village Limbungan, District Rumbai Pesisir. The tourist area has the potential to become the tourism icon in Pekanbaru due to its physical condition which still green and natural, and Bandar Khayangan Lake is the only lake in Pekanbaru. Facilities and infrastructure of recreation onBandar Khayangan Lake Tourist Area is still lacking so that the number of tourists is relatively small. The design method used is the result of field survey, literature study, and empirical data. The designing process of Bandar Khayangan Lake Tourist Area arrangementfocuses on water recreation, land recreation, family culinary, inn, and picnic while enjoying nature beauty. To optimize the potential of Bandar Khayangan Lake as the main recreation, the design theme used is waterfront architecture especially in recreation sector. This designfollows the waterfront architecture rules. The concept used in structuring tourist area is lotus, which is one of plants that lives in waters area of lake and has significant role in ecosystem of Bandar Khayangan lake. This concepts is a reference in the design of areas andbuildings. The result of this design is to present a lake attraction that can accommodate water and land recreation activities while maintaining the characteristic of this area.Keywords: Pekanbaru Attraction, Bandar Khayangan Lake , Waterfront Architecture